Enhancing patient informed consent in elective skin cancer surgeries: a comparative study of traditional and digital approaches in a German public hospital - Alexandra Schulz; Sabine Bohnet-Joschko (BMC, 2024)
Abstract Background This study aims to investigate the integration of modern sources of patient information, such as videos, internet-based resources, and scientific abstracts, into the traditional patient informed consent process in outpatient elective surgeries. The goal is to optimize the informed consent experience, enhance patient satisfaction, and promote shared decision making (SDM) between patients and surgeons. By exploring different patient informed consent formats and their impact on patient satisfaction, this research seeks to improve healthcare practices and ultimately enhance patient outcomes. The findings of this study will contribute to the ongoing efforts to improve the informed consent process in public hospitals and advance patient-centred care. Methods Data collection occurred at the day care clinic of a prominent German public hospital, forming an integral component of a prospective clinical investigation. The study exclusively focused on individuals who had undergone surgical intervention for skin cancer. For the purpose of meticulous data examination, the statistical software SPSS version 21 was harnessed. In the course of this study, a chi-square test was aptly employed. Its purpose was to scrutinize the nuances in patient experiences pertaining to informed consent across four distinct categories, viz., oral informed consent discussion (Oral ICD), written informed consent discussion (Written ICD), video-assisted informed consent discussion (video-assisted ICD), and digitally assisted informed consent discussion (digital-assisted ICD). The primary dataset of this inquiry was diligently gathered via a structured questionnaire administered to a targeted cohort of 160 patients. Within this sample, a balanced representation of genders was observed, encompassing 82 males and 78 females. Their collective age span ranged from 18 to 92 years, with an average age of 71 years. A randomized selection methodology was employed to include participants in this study during the period spanning from July 2017 to August 2018. Results Significant differences were observed across the groups for all research questions, highlighting variations in patient responses. Video-assisted and digital-assisted IC were rated as superior in patient satisfaction with information compared to written and oral IC. Demographic profiles of the four study groups were found to be comparable. Conclusion The findings of this study indicate that the incorporation of digital technologies in the informed consent process can enhance patient understanding during outpatient elective skin cancer surgeries. These results have important implications for increasing patient satisfaction and improving the SDM process within the hospital environment.